ANALISIS TINGKAT KESEHATAN BANK SEBELUM DAN SESUDAH MELAKUKAN MERGER DAN AKUISISI - admin, RADHA RIANTIKA B11112035 (Jurnal Manajemen Update, 2016)
This study aims to determine whether there is any difference in the level of health and financial performance of banks before and after mergers and acquisitions in the banking listed in the Indonesia Stock Exchange using the ratio of CAMEL are CAR (Capital Adequacy Ratio), NPL (Non Performing Loan), NPM (Net profit Margin), ROA (Return on Assets), ROE (Return on Equity), NIM (Net Interest Margin), and ROA (Operating Expenses to Operating Income) and LDR (Loan to Deposit Ratio) Analysis of differences in the level of health and performance bank finance before and after mergers and acquisitions using paired sample t test. Unknown t test results seen from the significance of the eight ratios are CAR, NPM, ROA, ROE, NIM, ROA, LDR and CAMEL scores that have a significant difference before and after mergers and acquisitions. While the NPL ratio has no significant difference before and after mergers and acquisitions. Keywords: CAMEL, CAR, NPL, NPM, ROA, ROE, NIM, ROA, LDR, and CAMEL Score.